ETIKA BISNIS E-COMMERCE BERDASARKAN MAQASHID SYARIAH PADA MARKETPLACE BUKALAPAK.COM - Diniarti Novi Wulandari; Budi Santoso; Handry Sudiartha Athar (Master of Management, Mataram University, 2017)
Islam has regulated all aspect of human life, one of them is e-commerce. During the development, the criminals also increase. This is because of a lot of violence of business ethics that is not in aware of five basics principles of life; religion, soul, descendents, logics, and wealth (maqashid sharia). The aim of this research to determine the implementation of business ethics and the implementation of maqashid sharia in Bukalapak.com. This research is using qualitative approach. To study the content, the writer analyzed the collected information through some evente registered in the websites of Bukalapak.com. The conclude this research is the implementation of business ethics have been done well as applied by Rasulullah SAW, as in maqashid sharia with four protection system has been applied to protect the rights of the customers. The recommendation of this research is that all regulation should be applied well. It is also necessary to make a board to control any transaction of e-commerce as to meet the principles of sharia and the regulation. Keywords : e-commerce, Bukalapak, business ethics, maqashid sharia